The Nasal Epithelium as a Route of Infection and Clinical Signs Changes, in Rainbow Trout (Oncorhynchus mykiss) Fingerlings Infected with Aeromonas spp - Fabián Ricardo Gómez de Anda; Vicente Vega-Sánchez; Nydia Edith Reyes-Rodríguez; Víctor Manuel Martínez-Juárez; Juan Carlos Ángeles-Hernández; Ismael Acosta-Rodríguez; Rafael German Campos-Montiel; Andrea Paloma Zepeda-Velázquez (Applied Sciences, 2021)
The genus Aeromonas is a group of bacteria that is widely distributed in water bodies and belongs to the normal intestinal microbiota of aquatic and terrestrial animals. In the present work, rainbow trout fingerlings were experimentally infected by an immersion bath with different Aeromonas species. Subsequently, the behavior of the infected groups was observed and recorded. Infected fingerlings were evaluated by histopathology. The highest percentages of hyperpigmentation (18.88%) and inappetence (47.7%) were observed in fish infected with A. salmonicida, while abnormal swimming (83.33%) was recorded in fish infected with A. bestiarum. In histopathological findings, the highest percentages were observed in the olfactory epithelium (50.0%) for A. lusitana and A. salmonicida (41.1%)-infected fish. While, in the nervous system, the cerebral hemispheres (31.1%) in A. media-infected fish and the oblongata medulla (40.0%) in the A. bestiarum-infected fish presented the highest percentages. Meanwhile, A. salmonicida and A. bestiarum have the highest pathogenicity and virulence based on the histopathological findings in the olfactory epithelium and nervous system. Due to the proximity of the olfactory epithelium with the nervous tissue, it is possible that the infection generated by the Aeromonas species and the histopathological findings in the nervous tissue are reflected in different behavioral changes that suggest differences in the pathogenicity and virulence of the bacteria.